Does specialisation impact sprint and change of direction performance in youth football players? - Zoellner, A.; Read, P.; Whatman, C.; Sheerin, K. (International Journal of Strength and Conditioning, 2026)
Purpose: Specialisation in youth football is common, often with the goal of heightened sporting success later in life. The purpose of this study was to investigate if sprint and change of direction (COD) performance differs between specialised and diversified youth football players.